Multiple Linier Regression Analysis Effects of Education Media on Student Experience and Satisfaction - Wibowo, Gunturari; D P, Bambang Purnomosidi; Andriyani , Widyastuti (Sinkron : jurnal dan penelitian teknik informatika, 2025)
The purpose of this study is to explore the effect of quiz- and game-based learning media on student learning experiences and satisfaction. This study models the relationship between media, motivation, experience, and learning satisfaction differently from previous studies with single variables. The research method uses a multiple linear regression approach with data collected through a Likert scale questionnaire. The research subjects consisted of 107 tenth-grade students majoring in Network and Computer Engineering at SMK Bhinneka Karya Simo. Data processing was carried out using Python and Microsoft Excel software for data analysis. The results showed that the variables of media, motivation, and response had a significant effect on learning experience (p < 0.05). The regression equations obtained were: experience (Y2) = 0.5918 + 0.2594X1 + 0.2840Y1, while satisfaction (Y3) = 0.5918 + 0.2594X1 + 0.2840Y1 + 0.3239Y2. In conclusion, learning experience is mainly influenced by media and motivation, while learning satisfaction is influenced by media, motivation, and the experience itself. These findings confirm that game-based learning strategies can create more meaningful learning experiences and encourage increased student satisfaction, which can be used as a basis for improving the quality of learning in the classroom.